Enhancing Community Income Through Women's Roles in Bukit Batu Tourism Village Development, Bengkalis Regency - Maryantina; Ika Fitria Hasibuan; Sefrona Syaiful; Eni Sumiarsih; Yuliati (Jurnal Sains Terapan Pariwisata, 2026)
This study aims to determine how community income increases through the role of women in the development of the Bukit Batu Tourism Village. New sources of income, income stability, increased assets, and participation in economic activities were examined. These activities included cultural attractions, managing tourism facilities, and participating in tourism organizations. The study used a descriptive, qualitative approach. Data were collected via observation, in-depth interviews, questionnaires, and documentation. There were 78 respondents, including Village Heads, members of Tourism Awareness Groups, tourism facility managers, and MSME actors. All participants were selected through a census. Data were analyzed descriptively using a Likert scale. The findings show that community income increased. Before their involvement in tourism, 44.74% earned IDR 2.5–3 million, and 5.26% earned ≤ IDR 2.5 million. After joining the tourism sector, 39.47% earned IDR 4-5 million, and no one remained in the ≤ IDR 2.5 million category. Women's participation in Cultural Attractions scored 3.16 (Fair). Involvement in Tourism Facilities scored 4.14 (Good), Handwoven Textile SMEs scored 4.10 (Good), Sago Cracker SMEs scored 4.22 (Very Good), and Traditional Cake Businesses scored 3.97 (Good). Community perception showed the greatest income growth in handwoven textile SMEs